Mechanistic Insights into Electrooxidative Allylation of a Carbamate in the Presence of Solid-Supported Acids - Haruka HOMMA; Natsumi HONJO; Akihiro TAKABAYASHI; Toshiki TAJIMA (Electrochemistry)
The electrooxidative allylation of a carbamate was successfully demonstrated using 3-propylsulfonic acid-functionalized silica gel (Si-SCX-2). It was shown that the electrochemical oxidation of the carbamate as a first step yields the corresponding N-acyliminium ion equivalent at room temperature, and the reaction of the N-acyliminium ion equivalent with allyltrimethylsilane as a next step leads to allylation without the use of Lewis acids. It was also found that the HBF4 generated by the cation exchange reaction between the Si-SCX-2 and the supporting electrolyte plays an important role in this reaction system.